Pemanfaatan Toga Usadha Bali bagi Pemuda Desa Adat Bitera Gianyar Menuju Era Normal Baru - Ketut Agus Adrianta; I Gusti Agung Ayu Kusuma Wardhani; Ni Nyoman Wahyu Udayani; Agung Ari Chandra Wibawa (Jurnal Pengabdian UNDIKMA, 2023)
This community service aims to increase knowledge and skills for the youth of the Bitera Gianyar traditional village regarding the use of TOGA (family medicinal plants) as well as provide training and assistance in making plant-based hand sanitizers in the yard of the house that can be used and used for preventive efforts against transmission the Covid-19 virus. The service method used was in the form of participatory training and small group discussions (SGD). The activity evaluation instrument was carried out using a questionnaire and statistically analyzed using a paired t-test. This community service activity increased participants' knowledge by 45.84%. The service participants, in general, understood the importance of vaccination for the human body and how to use materials around the environment as natural hand sanitizers. Increasing the ability and knowledge of the Bitera Gianyar traditional village's youth is expected to change people's behavior; henceforth, the participants will become agents of change who will influence their environment to adopt a healthy lifestyle.